500 W rod-type 4 × 4 multicore ultrafast fiber laser - Klenke, Arno; Steinkopff, Albrecht; Aleshire, Christopher; Jauregui, Cesar; Kuhn, Stefan; Nold, Johannes; Hupel, Christian; Hein, Sigrun; Schulze, Steffen; Haarlammert, Nicoletta; Schreiber, Thomas; Tuennermann, Andreas; et al. (Optics Letters, 2022)
We present a coherently combined femtosecond fiber chirped-pulse-amplification system based on a rod-type, ytterbium-doped, multicore fiber with 4 × 4 cores. A high average power of up to 500 W (after combination and compression) could be achieved at 10 MHz repetition rate with excellent beam quality. Additionally, < 500 fs pulses with up to 600 µJ of pulse energy were also realized with this setup. This architecture is intrinsically power scalable by increasing the number of cores in the fiber.
CRIS-Team Scopus Importer:2023-04-20